The Development Of Food Truck Decision Making System - Hasbullah, Siti Salwa; Abd Hamid, Siti Nurhairiya (Journal of Computing Technologies and Creative Content, 2017)
Food Truck Decision Making System is an online web application primarily used for the entrepreneur’s food trucks industry in Malaysia. Nowadays, Malaysian entrepreneur’s community does not have any dedicated platform to the entrepreneur food truck business community that offer a specific online web application for entrepreneur food truck business to explore and identify an appropriate type, design and facilities for food truck. Entrepreneur’s need a new web application provides decision making information for the food trucks business including the package, designing, price and others. The aim of this system develop is to become an efficient and effective online that provided primarily to the Malaysian entrepreneur food trucks market. Objective of this Food truck Decision Making System is to study the needs of food trucks for Malaysian entrepreneurs in developing the Food Truck decision Making System. By implementing this system, it helps the entrepreneur who interested involve the business food trucks easier to choose the food truck design and package that required for their needs and expectation under different categories. In addition, it also can incourage the current market food truck get high request and promotes the food truck industry among entrepreneurs who interested in food truck business.